Unveiling alfalfa root rot resistance genes through an integrative GWAS and transcriptome study - Fei He; Ming Xu; Hao Liu; Yanchao Xu; Ruicai Long; Junmei Kang; Qingchuan Yang; Lin Chen (BMC Plant Biology)
Abstract Background Root rot is a major disease affecting alfalfa (Medicago sativa L.), causing significant yield losses and economic damage. The primary pathogens include Fusarium spp., Rhizoctonia spp., Pythium spp., and Phytophthora spp., with Fusarium being particularly severe. Breeding disease-resistant varieties is crucial for mitigating these losses. Results Under conditions of inoculation with Fusarium oxysporum, we conducted a statistical analysis of six phenotypic traits in alfalfa. Significant phenotypic variation was observed among different alfalfa varieties. Correlation analysis revealed significant relationships among traits such as relative yield, relative plant height (PH), and relative root number (NR), indicating potential synergistic roles of these traits in disease resistance. Through GWAS analysis, we identified 41 significant single nucleotide polymorphisms (SNP) associated with root rot resistance across eight chromosomes. The transcriptome analysis identified multiple differentially expressed genes (DEGs) associated with root rot stress, including transcription factors such as WRKY, NAC, AP2, GRAS, HLH, B3, MYB, and ARF. By integrating GWAS and transcriptome data, we identified four key DEGs significantly associated with root rot resistance, offering valuable insights for developing disease-resistant alfalfa varieties and enhancing overall crop resilience. Conclusion Our study identified significant phenotypic variation and key correlations among traits under root rot stress in alfalfa. We pinpointed 41 significant SNPs associated with root rot resistance across eight chromosomes and identified several key DEGs, including WRKY, NAC, and MYB transcription factors. The integration of GWAS and RNA-Seq data identified four key DEGs associated with root rot resistance, providing valuable insights for breeding disease-resistant alfalfa varieties and enhancing crop resilience.